High voltage repetitive pulsed power generator by using modular multilevel converter. Issue 4 (19th May 2019) - Madichetty, Sreedhar; Mishra, Sukumar
ABSTRACT: This paper proposes the development of silicon carbide junction field effect transistor-based high-frequency link (HFL) modular multilevel converter (MMC). HFL has been used in conjunction with MMC to achieve higher current density with less foot print, which is the main requirement for exhaust gas treatment. The proposed system has been developed for various scalable ranges such as 6, 8 and 10 modules per arm to generate square wave unipolar/bipolar pulse and exponential decay pulses. These pulses have been generated for 1 kV/cm with 100 µs and 1000 µs and tested. The proposed system has been developed mathematically and simulated in Matlab/Simulink. Thus, obtained results have been verified by conducting an experiment on 3 kV prototype and results are explored.